1934
DOI: 10.1084/jem.60.6.687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hemacytological Constitution of Male and Female Rabbits

Abstract: Previous reports from this laboratory on the hemacytological constitution of the rabbit have been limited to observations on male animals. These studies have now been extended to normal females and to females presenting various defects referable to constitutional (hereditary) or environmental influences. It is the purpose of the present paper to present one aspect of these studies; namely, a comparison of the blood cytology of normal male and female litter mates. These comparisons were made in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1936
1936
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Wintrobe, Shumacker & Schmidt (1935-6) carefully studied the blood of considerable numbers of dogs, rabbits and rats. Though they found that there was a greater concentration of haemoglobin in the blood of dogs than in the blood of bitches, they did not confirm the claims of Rosahn et al (1934) that buck rabbits had a greater concentration of haemoglobin in their blood than had doe rabbits. The mean concentration of haemoglobin in the blood of female rats was slightly greater than that in the blood of male rats.…”
Section: I954mentioning
confidence: 81%
See 1 more Smart Citation
“…Wintrobe, Shumacker & Schmidt (1935-6) carefully studied the blood of considerable numbers of dogs, rabbits and rats. Though they found that there was a greater concentration of haemoglobin in the blood of dogs than in the blood of bitches, they did not confirm the claims of Rosahn et al (1934) that buck rabbits had a greater concentration of haemoglobin in their blood than had doe rabbits. The mean concentration of haemoglobin in the blood of female rats was slightly greater than that in the blood of male rats.…”
Section: I954mentioning
confidence: 81%
“…Readings on a few wild birds, however, were higher and then the effect of sex was not obvious. Rosahn, Pearce & Hu (1934) found that buck rabbits had a significantly greater concentration of haemoglobin in their blood than had virgin doe rabbits of the same litter. Vaulont (1935) found that the mean haemoglobin concentration in the blood of ten female cats was 12.56 g/Ioo ml., whereas that in the blood of ten tom cats was 13-07 g/Ioo ml.…”
Section: I954mentioning
confidence: 95%
“…This study on blood cytology has been extended in various directions and the influence of such factors as disease (5), breed (6), sex (7), age, certain physiological states, and diet has been investigated. The present paper is the report of observations made on laboratory bred strains of standard varieties of rabbits.…”
mentioning
confidence: 99%
“…Likewise male gerbils also had higher RBC and haemoglobin but shorter bleeding time (tables 2 and 3). Simi!.ar sex differences in blood parameters has been reported for other mammals (Rosalin et al 1934;Winthrobe 1933;Anderson and Gee 1958;Arafa et al 1974;Rahaman et al 1975). However both Sealander (1964), WiUiamson and Pelton (1976) failed to observe sex-dependent variations for RBC, WBC, packed cell volume (PCV), haemoglobin and platelets in several small mammals and European wild hogs respectively.…”
Section: Resultsmentioning
confidence: 91%